2019
DOI: 10.1140/epjc/s10052-019-7042-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrically charged strange quark stars with a non-linear equation-of-state

Abstract: The properties of electrically charged strange quark stars are investigated. We assume a non-linear equation-of-state, and we obtain numerical solutions to the structure equations. The key features of the solutions obtained here are (i) they can support a 2 solar masses star, (ii) both the mass and the electric charge of the stars increase with the α parameter characterizing the electric density, (iii) the electric object is heavier and larger than its neutral counterpart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…In recent progress, Ivanov [71] assumed a linear EoS to study charged perfect fluid solutions. Motivated by this results, several authors have studied electrically charged fluid spheres for linear and non-linear EoS [72][73][74][75][76]. Motivated by MIT bag models of strange stars, charged solutions were studied by some authors [77,78].…”
Section: Introductionmentioning
confidence: 99%
“…In recent progress, Ivanov [71] assumed a linear EoS to study charged perfect fluid solutions. Motivated by this results, several authors have studied electrically charged fluid spheres for linear and non-linear EoS [72][73][74][75][76]. Motivated by MIT bag models of strange stars, charged solutions were studied by some authors [77,78].…”
Section: Introductionmentioning
confidence: 99%
“…[32] using a simplified approach (see also Refs. [31,[33][34][35]). Electrically charged hybrid stars were previously studied in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31], the surface of a SQS has a high electric field, which can reach about 1 × 10 21 V=m. The results presented in [30][31][32] using the massless version of the MIT bag model and a nonlinear EoS, respectively, have demonstrated that charged stars are heavier than their neutral counterparts, with the increasing in the maximum mass being dependent of the magnitude of the electric charge. As a consequence, the presence of the electric charge can modify the star compactness, given by the ratio between its mass and radii (M=R), which determines tidal deformability.…”
Section: Introductionmentioning
confidence: 99%